(untitled) (Fiep Bulletin - online, 2011)
The hospital environment offers risks of accidents and illnesses to workers. In this view and in order to know the reality of accidents with perforating-cutting instruments in a university hospital in Natal / RN, we aimed to characterize the accidents with cutting and piercing material recorded in a general hospital in Natal / RN, period set 2006 to set/2008, by labor sector and year of occurrence; identify the professional category that was most affected by accidents with perforating-cutting instruments, as recorded by HICC; and to identify the professional category, among those which made use of PPE’s, most affected by accidents with perforating-cutting instruments in a general hospital in Natal / RN. This is an exploratory-descriptive study with retrospective data and quantitative approach. Results were: the units (wards) represented the hospital sector where most accidents occurred of biological type (55.4%); the year of 2007 (30.4%) as the one with most detected accidents; practical nursing staff (82.1%) were the professional category more victimized, and nursing technicians as to the ones who had the highest number of accidents, even among those who made use of PPE’s.